TO THE QUESTION OF THE METHODOLOGY OF CONDUCTING LONG-TERM EXPERIMENTS ON THE NO-TILL TECHNOLOGY INFLUENCE ON SOIL PROPERTIES - S. A. Yudin; V. P. Belobrov; V. K. Drediger; A. M. Grebenikov; A. J. Aydiev; B. S. Ilyin; N. R. Ermolaev (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
When setting a long-term field experiment in order to study the impact of direct sowing technology on soil properties it is necessary to take into account not only the known requirements, but a comprehensive analysis of soil heterogeneity as well. The article presents the results of detailed topographic and soil-agrochemical mapping with estimation of variability of morphological and agrochemical properties of typical chernozems studied on four experimental fields of 2.4 ha area each.